Neuroblastoma estágio 4S e hepatomegalia maciça: relato de caso - Ricardo Pasquini Neto; Ana Julia Pereira de Paula; Fernanda de Almeida Vieira; Hadelle Habitzreuter Hassmann; Ana Paula Kuczynski (Sociedade Brasileira de Pediatria, 2024)
OBJECTIVE: To report a case of stage 4S neuroblastoma and massive hepatomegaly that worsened the disease prognosis. CASE REPORT: A 3-month-old male infant presented with 7 days of worsening abdominal distension, significant sweating, incessant crying, and irritability. His abdomen was globular and exhibited massive hepatomegaly. Imaging examinations detected multiple nodules in the liver parenchyma and a hypoechoic nodule in the right adrenal gland. The lesions were biopsied, with findings revealing infiltrative neuroblastoma in the liver tissue. The patient was diagnosed with International Neuroblastoma Staging System stage 4S, and treatment was started according to the International Society of Paediatric Oncology - Paediatric Oncology in Developing Countries protocol. During the first chemotherapy cycle, his condition required prolonged mechanical ventilation and hemodialysis. It was then decided to switch to the POG 9341-Modified regimen in an emergency mode. A significant clinical improvement response was observed after the third chemotherapy cycle. Subsequent cycles were administered based on the initial proposed protocol. Complete remission was achieved after the eighth cycle. DISCUSSION: Stage 4S neuroblastoma usually has a good prognosis; however, when associated with massive hepatomegaly, the prognosis becomes unfavorable. Complications during the first chemotherapy cycle required a change in management to the POG 9341-Modified regimen, which resulted in a reduction in the number and size of hepatic and adrenal nodules. Owing to significant clinical improvement, the remaining cycles were performed using the initial protocol. Despite the uncommon association and the lack of consensus for a specific treatment, complete remission was achieved by combining therapeutic regimens.